THE EFFECT OF CORPORATE IMAGE AND PRICE FAIRNESS ON GOJEK USER LOYALTY AND SATISFACTION - Dinda Anisa Meldya Salsabila; Felicia Immanuela; Kurnia Hotmaida Sianturi; Yohanes Farrell Pamungkas (Universitas Pelita Harapan, 2022)
This study aims to realize the influence of tariffs, and company image related to customer loyalty of online-based public transportation services to Gojek customers. The process model used during this research is the perception of causality and the perception of causality and the number of respondents in this study is 120 respondents. In research conducted based on perceived causality (perceived causality) according to a partial way a significant effect on customer loyalty. The results of this study prove that the company's image affects customer satisfaction and customer loyalty, therefore it affects positively on the fairness of a price.